The Effect of Utilizing the Google Site as a Learning Resource and Learning Motivation on Learning Outcomes in Economics Subject at SMAN 1 Tembilahan Hulu - Muhammad Iqbal; Gusnardi Gusnardi; Hendripides Hendripides (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effect of using the Google site as a source of learning and learning motivation on learning outcomes in economics subjects at SMAN 1 Tembilahan Hulu. This type of quantitative descriptive research. The sample in this study was students of class XI IPS for the 2022/2023 academic year, which consisted of 4 classes with a total of 130 students. Data were collected using questionnaires and documentation which were then analyzed using multiple linear regression data analysis techniques and the coefficient of determination. The results showed that the use of the Google site as a source of learning and learning motivation had a significant positive effect on learning outcomes with an effect of 12.6% and the rest was influenced by other factors not discussed in this study such as student learning independence. Thus it can be concluded that student learning outcomes will increase if the Google site as a learning resource is utilized optimally, this will have a positive influence on learning outcomes.